An improved split-stepwavelet transform method for anomalous radiowave propagation modeling - Iqbal, A. (Czech Technical University, 2014)
An Anomalous tropospheric propagation caused by ducting phenomenon is a major problem in wireless communication. Thus, it is important to study the behavior of radio wave propagation in tropospheric ducts. The Parabolic Wave Equation (PWE) method is considered most reliable to model anomalous radio wave propagation. In this work, an improved Split Step Wavelet transform Method (SSWM) is presented to solve PWE for the modeling of tropospheric propagation over finite and infinite conductive surfaces. A large number of numerical experiments are carried out to validate the performance of the proposed algorithm. Developed algorithm is compared with previously published techniques; Wavelet Galerkin Method (WGM) and Split-Step Fourier transform Method (SSFM). A very good agreement is found between SSWM and published techniques. It is also observed that the proposed algorithm is about six times faster than WGM and provide more details of propagation effects as compared to SSFM.